(untitled) (Journal of Pathology of Nepal, 2025)
Background: Sarcomatoid carcinoma is a rare and aggressive variant of squamous cell carcinoma, accounting for 3% of all squamous cell carcinomas in the head and neck region, characterized by dysplastic surface squamous epithelium and an invasive spindle cell component. Materials and Methods: The study was conducted over six years (2017-2022) at the Gujarat Cancer and Research Institute, and a total of 117 cases of sarcomatoid carcinoma in the head and neck region were included, comprising resected specimens, biopsies, and cases reviewed from external institutions. Results: The median age at presentation was 49 years, with predominance in males (male: female 3.5:1). The most common sites were the buccal mucosa (44.4%), tongue (20.5%), and larynx (10.2%), typically presenting as proliferative or ulceroproliferative lesions with a polypoidal appearance. Immunohistochemistry, performed in 86 cases, revealed immunoreactivity to epithelial markers (EMA, p40, p63, CK5/6, AE1/AE3) in the majority of cases. In the resected specimen, over half of the patients (53.3%) presented with early T-stage disease (T1: 15.6%, T2: 37.8%), and 60% had no lymph node involvement (N0). Various treatment modalities were employed, including primary surgical resection (20.8%), neoadjuvant chemotherapy followed by surgery, and palliative care. The two-year survival rate was 43.8%, with recurrence observed in seven patients and one case of distant metastasis to the lung during the follow-up period. Conclusions: Sarcomatoid carcinoma of the head and neck is a rare but aggressive variant of squamous cell carcinoma that requires careful histopathological and immunohistochemical evaluation for accurate diagnosis due to its resemblance to other spindle cell tumors. Early-stage detection and timely intervention are crucial for improving patient outcomes. Despite diverse treatment approaches, the prognosis remains guarded, underscoring the need for heightened clinical awareness and further research to optimize management strategies.